OPG/RANKL/RANK axis is a critical inflammatory signaling system in ischemic brain in mice - Shimamura, Munehisa (National Academy of Sciences, 2014)
Osteoprotegerin (OPG) is a soluble secreted protein and a decoy receptor, which inhibits a receptor activator of nuclear factor κB (NF-κB) ligand (RANKL)/the receptor activator of NF-κB (RANK) signaling. Recent clinical studies have shown that a high-serum-OPG level is associated with unfavorable outcome in ischemic stroke, but it is unclear whether OPG is a culprit or an innocent bystander. Here we demonstrate that enhanced RANKL/RANK signaling in OPG(−/−) mice or recombinant RANKL-treated mice contributed to the reduction of infarct volume and brain edema via reduced postischemic inflammation. On the contrary, infarct volume was increased by reduced RANKL/RANK signaling in OPG(−/−) mice and WT mice treated with anti-RANKL neutralizing antibody. OPG, RANKL, and RANK mRNA were increased in the acute stage and were expressed in activated microglia and macrophages. Although enhanced RANKL/RANK signaling had no effects in glutamate, CoCl(2), or H(2)O(2)-stimulated neuronal culture, enhanced RANKL/RANK signaling showed neuroprotective effects with reduced expression in inflammatory cytokines in LPS-stimulated neuron-glia mixed culture, suggesting that RANKL/RANK signaling can attenuate inflammation through a Toll-like receptor signaling pathway in microglia. Our findings propose that increased OPG could be a causal factor of reducing RANKL/RANK signaling and increasing postischemic inflammation. Thus, the OPG/RANKL/RANK axis plays critical roles in controlling inflammation in ischemic brains.